Risk for acquired coronary artery disease in genetic vs. congenital thoracic aortopathy - Dolmaci, Onur B.; Ayyildiz, Tugay; Poelmann, Robert E.; Driessen, Antoine H. G.; Koolbergen, Dave R.; Klautz, Robert J. M.; Lindeman, Jan H. N.; Grewal, Nimrat (Frontiers in Cardiovascular Medicine, 2023)
Objective Patients with Marfan syndrome (MFS) and patients with a bicuspid aortic valve (BAV) have a significantly increased risk to develop thoracic aortopathy. Both conditions share many pathophysiological mechanisms leading to aortic complications. Bicuspidy is known to have a low risk for acquired coronary artery sclerosis. The aim of this study is to determine the risk of coronary sclerosis in MFS patients. Methods MFS patients with an aortic root dilatation, which were surgically treated between 1999-2017, were included and matched with BAV and tricuspid aortic valves (TAV) patients based on sex and age. Cardiovascular risk profiles were determined in all three groups. Coronary sclerosis was graded in all patients on coronary imaging (coronary angiography or computed tomography) using a coronary artery scoring method, which divides the coronaries in 28 segments and scores nonobstructive (20%–49% sclerosis) and obstructive coronary sclerosis (>49% sclerosis) in each segment. Results A total of 90 matched patients (30 within each group) were included. MFS patients showed less cardiovascular risk factors compared to BAV and TAV patients. TAV patients had higher amounts of obstructive coronary sclerosis as compared to BAV patients (p=0.039) and MFS patients (p=0.032). No difference in non- and obstructive coronary artery disease was found between the MFS and BAV population. Conclusion MFS and BAV patients have a significantly lower risk for, and prevalence of coronary artery disease as compared to TAV individuals.